The teacher on the internet Self-efficacy beliefs, usage, and attitudes - Simon, Audrey B. (Transactions of the National Academy of Science and Technology, 2011)
This study examined the relationship between and among teachers' self-efficacy beliefs, usage, and attitude towards the internet with their personal characteristics such as age, number of years in teaching, computer literacy level, and trainings attended. A descriptive method of research was used in finding answers to the problems of this study while random sampling method was applied to select the 124 teacher participants from nine campuses of the Isabela State University. This study used a four-part questionnaire and a five-point Likert-type sale in gathering and in interpreting the data. The first part was used to collect the teachers' personal characteristic. The second part measured the teacher's Internet self efficacy. The third part gathered data on the internet usage of the teachers, and the fourth part measured their attitude towards the internet. Negatively stated attitude questions were scored in reverse order. Teacher participants were given one week to complete the questionnaire before the researcher personally retrieved them. The responses were tallied and presented using frequency distribution, weighted mean and percentage distribution. The Pearson Product Moment correlation was used to determine the significant relationships and correlations between and among the variables. It has been found that: 1) the older the age and the longer a teacher had been in the teaching profession, the less comfortable he or she was in using the internet; 2) a high computer literacy level and in-service trainings influenced the teachers' frequency of Internet use, high self-efficacy and positive attitude towards the internet; 3) teachers frequency of internet use increased their self-efficacy and attitude while, while a highly positive attitude motivated teachers to frequently use the internet and increased their self-efficacy; and 4) the more problems the teachers encountered the lesser their usage, the lower their self-efficacy, and the more negative their attitudes were.